Improved Corrosion Resistance on Selective Laser Melting Produced Ti-5Cu Alloy after Heat Treatment - Qin, P.; Liu, Y.; Sercombe, T.; Li, Y.; Zhang, C.; Cao, C.; Sun, Hongqi; Zhang, L. (2018)
A Ti-5Cu alloy produced by selective laser melting exhibits a nonuniform Ti2Cu phase structure, which contains a small amount of a' phase in melt pool boundaries thereby resulting in reduced corrosion resistance. The heat-treatment process proposed in this work eliminates the deleterious effect of a' phase and the Ti2Cu phase is refined using different cooling rates, which improves the corrosion resistance. The electrochemical results indicate that the heat-treated Ti-5Cu samples have similar corrosion behavior to pure CP-Ti. A slower cooling rate produces a larger spacing between the Ti2Cu phases in the microstructure of the sample, resulting in higher corrosion resistance. The corrosion behavior of SLM-produced Ti-5Cu and heat-treated counterparts with different microstructure are detailed discussed.